Intellectual Capital in SMEs: A Bibliometric Study and Directions for Future Research - Anggraini, Raden Isma; Maarif, Mohammad Syamsul; Sukmawati, Anggraini; Asikin, Zenal (Indonesian Journal of Business and Entrepreneurship, 2025)
Background: Intellectual capital (IC) has been recognized as a key driver of business performance and sustainability, particularly for small and medium enterprises (SMEs). IC, which comprises human capital, structural capital, and relational capital, plays a crucial role in fostering innovation, improving knowledge management, and enhancing competitive advantage. However, the comprehensive evolution of IC research in SMEs remains underexplored.Purpose: This research seeks to examine the evolution of intellectual capital (IC) studies in small and medium-sized enterprises (SMEs) over the last ten years, pinpoint major contributors, investigate prevailing themes, and uncover emerging directions in the field.Design/Methodology/Approach: This study uses bibliometric analysis with a database sourced from Scopus and uses VOSviewer for visualization. The study applied various bibliometric techniques, including citation analysis, co-word analysis, and bibliographic coupling, to map the intellectual landscape of IC research in SMEs.Findings/Results: The analysis reveals that IC research in SMEs has grown significantly, with an increasing focus on human, structural, and relational capital. Key research themes include innovation, knowledge management, financial performance, and sustainability. The study also identifies Indonesia, Pakistan, Poland, and Portugal as leading contributors to IC research, reflecting the global recognition of knowledge-based economic growth. The study also observes a significant shift toward IC integration with digital transformation and artificial intelligence.Conclusion: This research offers beneficial perspectives for academics, policymakers, and business practitioners by emphasizing the strategic role of IC in SMEs' sustainability. The findings suggest that future research should further explore the intersection of IC with digital transformation and AI-driven business models.Originality/Value (State of the Art): This study is among the first to provide a comprehensive bibliometric analysis of IC research in SMEs, mapping its chronological development and identifying future research directions. Keywords: bibliometric analysis; competitive advantage; digital transformation; intellectual capital; small and medium enterprises (SMEs)